الثآليل التناسلية: مقارنة علاجية بين التطبيق الموضعي لكل من محلول ماءات البوتاسيوم بنسبة 5% والآزوت السائل - حسن, فوز; صالح, حسن; سعود, ليلى (Latakia University Journal -Medical Sciences Series, 2018)
مقدمة : تعد الثآليل التناسلية أشيع الأمراض المنتقلة جنسيا حول العالم. تهدف جميع الوسائل العلاجية الى تدمير الآفات الظاهرة للعيان، من بينها الآزوت السائل ومحلول ماءات البوتاسيوم. الهدف :مقارنة محلول ماءات البوتاسيوم الموضعي بنسبة 5% بالمعالجة القرية بالآزوت السائل في علاج الثآليل التناسلية. المواد و الطرق :هذه دراسة مستقبلية شملت 83 مريض (25 انثى و58 ذكر) تراوحت أعمارهم ما بين 18- 74 سنة من مراجعي العيادات الجلدية والتناسلية في مشفى تشرين الجامعي/ محافظة اللاذقية/سوريا , في الفترة الممتدة ما بين حزيران 2016 حتى حزيران 2017. تم تقسيم المرضى الى مجموعتين بشكل عشوائي: المجموعة الأولى:مرضى عولجوا بالآزوت السائل تطبيق من قبل الطبيب في عيادة الأمراض التناسلية مرة واحدة كل أسبوعين.. المجموعة الثانية: مرضى عولجوا بمحلول هيدروكسيد البوتاسيوم 5% حيث تم إعطاء المرضى كمية 10 مل من المحلول وتم تطبيقه مرة يوميا مساء تم تكرار العملية مرة كل أسبوعين حتى زوال الاندفاعات كليا أو بمدة لا تتجاوز ثلاثة أشهر أوصي مرضى كلتا المجموعتين بزيارات دورية مرة كل 15 يوم حتى زوال الاندفاعات بشكل كامل على ألا تتجاوز مدة العلاج ثلاثة أشهر. تمت متابعة المرضى بعد انتهاء مدة العلاج مرة شهريا لمدة ثلاثة أشهر سجلت فيها: نكس الاندفاعات السابقة, ظهور اندفاعات جديدة. النتائج :كان متوسط المدة الزمنية اللازمة لتحقيق الشفاء عند مرضى المجموعة الأولى 47.12 يوما بانحراف معياري قدره 22.95 يوم. بينما بلغ متوسط المدة الزمنية اللازمة لتحقيق الشفاء عند مرضى المجموعة الثانية 34,87 يوما بانحراف معياري قدره 19,83 يوم. (p-value= 0.014). الخلاصة : إن محلول ماءات البوتاسيوم ذو فعالية مماثلة ومدة شفاء أقصر من الآزوت السائل. Introduction :Genital warts are the most common sexually transmitted diseases around the world. All therapeutic means aim to destroy visible pests, including liquid nitrogen and potassium hydroxide. Aim :Comparison of topical potassium hydroxide solution 5% with the treatment of liquid nitrogen in the treatment of genital warts. Materials and Methods :This prospective study included 83 patients (25 females and 58 males) ranging in age from 18 to 74 years at the Tishreen University Hospital / Lattakia / Syria, between June 2016 and June 2017. Patients were divided into two groups: Group I: Patients treated with liquid nitrogen Apply by the doctor once every two weeks.Group II: Patients treated with 5% potassium hydroxide solution. Patients were given 10 ml of solution and applied once daily in the evening. The process was repeated every two weeks until the eruptions disappeared completely and not exceeding three months Patients in both groups were recommended for periodic visits every 15 days until the rashes were completely eliminated, and the duration of treatment should not exceed three months. Patients were followed after the treatment period once a month for three months in which they recorded: reversing previous eruptions, Appearance of new eruptions. Results :The recovery rate for the first group was: The recovery rate of the second group was: The mean time for recovery in patients in the first group was 47.12 days with a standard deviation of 22.95 days. While the mean time for recovery in patients in the second group was 34.87 days with a standard deviation of 19.83 days. The value of p was 0.014 Conclusion : Potassium saline solution is more effective and has a shorter cure period than liquid nitrogen.